Here on earth - Piznarski, Mark (Quezon City, 2000)
Chris Kelin (American Pie) and Leelee Sobieski (Never Been Kissed) star in a "heartfelt story of romance, friendship and true love." (JUMP Magazine) Rich Kid Kelley Morse (Klein) thought he had it all- money, good looks and a new Mercedes. But after a reckless car race destroys a roadside diner, Kelley finds himself sentenced to a summer of manual labor in a small town. That's where he meets and falls in love with a girl from the other side of the tracks, Samatha, But everything changes when Samantha's long-time boyfriend Jasper (Josh Hartnett, The Faculty) uncovers their secret romance. This "Sweet and romantic" (YOUNG MISS Magazine) tale of first love will capture your heart.